Wearing Muslimah Attire as an Expression of Preserving Personal Dignity and a Servant’s Obedience to Islamic Law - Buyung; Jasiah (Yayasan Payungi Smart Madani, 2025)
Clothing for a Muslim woman is not merely a covering for the body, but rather a manifestation of adherence to Islamic law, which has spiritual, moral, and social dimensions. Modern phenomena demonstrate the tension between the demands of fashion/popular culture and the principles of Islamic law regarding dress. This study aims to analyze in depth the legal status of Muslim women's dress in Islam, identify the dimensions of obedience and spirituality in the practice of covering the genitals, and examine the role of Muslim clothing as a means of maintaining self-respect (al-`iffah) amidst contemporary social challenges. This study uses the method qualitative with the approach library research And analysis of Fiqh (Islamic law). Primary data sources include the Qur'an (especially QS. An-Nur: 31 and QS. Al-Ahzab: 59) and the Hadith of the Prophet, while secondary data comes from tafsir books, classical fiqh, as well as contemporary scientific journals and literature related to the ethics of Muslim women's dress. The results of the study indicate that the obligation for Muslim women to dress according to sharia (covering all aurat except the face and palms, not tight, not transparent, not resembling men's clothing, and not excessive) is a law that qath'I (definitely) in Islam. Shar'i clothing has a dual function: as symbol of servant obedience to the command of God and as protector of self-respect